Agricultural markets mechanisms, failures, and regulations - Martimort, David (New York : Elsevier Science, 1996)
This volume aims at covering the variety of issues lying at the intersection of the modern theory of Industrial Organization and of the more traditional Agricultural Economics. The book is divided into three main sections. Each of them includes contributions which are particularly relevant for a better understanding of one or several of the following key issues: the organization of agriculture and its mechanisms, the extent of the market power in agri-food industries and, more generally, the failures of agricultural markets, and finally the nature of government's intervention in these markets.
Why do firms simultaneously purchase in spot and contract markets? Evidence from the United States steam coal market / Frank A. Wolak -- Dynamic models of oligopoly in rice and coffee export markets / Jeffrey M. Perloff -- New estimates of welfare and consumer losses in U.S. food manufacturing / Everett B. Peterson -- Explaining the causal relationship between farm and retail prices / Thomas W. Hertel -- Cartel quotas under majority rule / Stephen W. Salant -- The transaction cost approach to agricultural contracts / Dean Lueck -- Incorporating industrial organization into agricultural trade modelling / Ian M. Sheldon -- GATT agricultural policy reform : a United States perspective / Gordon Rausser -- Trade and storage / Ronald W. Anderson -- Environmental policies and induced innovation : the case of agriculture / David G. Abler -- Guilty until proven innocent : regulation with costly and limited enforcement / Joseph E. Swierzbinski -- Divide and conquer price discrimination lin entry gaines with strategic buyers / Richard J. Sexton -- Establishing vertical strategic alliances : case studies and heuristics / Helen McKay -- Reflections on the economic organization of agriculture : traditional, modern and transitional / Marc Nerlove.
Proceedings of a conference held at Institut d'economie industrielle, Toulouse in October 1993.
Includes bibliographical references.
Description based on print version record.
Keywords: Food industry and trade -- Congresses; Agriculture -- Economic aspects -- Congresses; Agriculture and state -- Congresses; Business & Economics -- Commerce; Business & Economics -- Economics -- General; Agriculture & related industries; Microeconomics